2009
DOI: 10.4238/vol8-2gmr601
|View full text |Cite
|
Sign up to set email alerts
|

α-Thalassemia (3.7 kb deletion) in a population from the Brazilian Amazon region: Santarém, Pará State

Abstract: ABSTRACT. The ethnic composition of the Brazilian population favors high frequencies of the -α3.7 deletion, responsible for α-thalassemia, because this mutation is very common in African populations. In spite of its importance, this hemoglobinopathy has been poorly investigated in Brazil, especially at the molecular level. We investigated the prevalence of the -α3.7 mutation in 220 individuals attended at the Municipal Hospital of Santarém, in the State of Pará. These patients were distributed into three diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
4
16
1
1
Order By: Relevance
“…As expected in admixed populations such as the African Brazilians investigated here, this allele frequency was somewhat lower than in African populations, where the frequency of -α 3.7 α-thalassemia ranges from 16.8% in Guinea-Bissau (Masmas et al , 2006) to 24% in Senegal (Migot-Nabias et al , 2006). The frequency of the -α 3.7 allele in this study was similar to that of three out of four Brazilian populations of African ancestry investigated by others (Sonati et al , 1991; Adorno et al , 2005), despite different degrees of African admixture, and much higher than the prevalence described in northern Brazil (7%) where Amerindian admixture is higher than African admixture (Souza et al , 2009). …”
supporting
confidence: 87%
See 1 more Smart Citation
“…As expected in admixed populations such as the African Brazilians investigated here, this allele frequency was somewhat lower than in African populations, where the frequency of -α 3.7 α-thalassemia ranges from 16.8% in Guinea-Bissau (Masmas et al , 2006) to 24% in Senegal (Migot-Nabias et al , 2006). The frequency of the -α 3.7 allele in this study was similar to that of three out of four Brazilian populations of African ancestry investigated by others (Sonati et al , 1991; Adorno et al , 2005), despite different degrees of African admixture, and much higher than the prevalence described in northern Brazil (7%) where Amerindian admixture is higher than African admixture (Souza et al , 2009). …”
supporting
confidence: 87%
“…In another survey in a highly admixed northeastern population the -α 3.7 /αα genotype was detected in 20% of 514 newborn babies while the homozygous genotype was seen in 2.5% of the children investigated (Adorno et al , 2005). In a recent study, the frequency of the -α 3.7 /αα genotype in a healthy admixed northern Brazilian population was 7% (Souza et al , 2009). The present study was done to determine the prevalence of α-thalassemia in southern Brazilians of African and European ancestry and in a sample of patients with mild anemia, microcytosis and normal iron status from the same population.…”
mentioning
confidence: 96%
“…When we analyzed the sub-sample with African ancestry, the α −3.7 mutation carrier frequency increased and was 6.5% higher than that for the whole sample but, as expected from the admixture, was lower than that observed in parental African populations, where the frequency of α-thalassemia carriers ranges from 11% to 50% (Weatherall and Clegg, 2001). The α −3.7 mutation carrier frequency in the sub-sample with African ancestry was also lower than that observed in Afro-Brazilian populations, where the carrier frequency ranges from 7% to 21% (Sonati et al , 2001; Adorno et al , 2005; Souza et al , 2009; Wagner et al , 2010), possibly because of a higher non-African admixture in this Afro-Uruguayan population. The α-thalassemia frequencies for Afro-descendants with microcytosis (33.3%) and the group of children with microcytosis and hypochromia (32.3%) were both similar to the frequency observed in a similar sample from the southern Brazilian state of Rio Grande do Sul (31.7%) (Wagner et al , 2010) and lower than that observed for a population in southeastern Brazil in which α-thalassemia explained about 50% of the cases of microcytosis (Borges et al , 2001).…”
Section: Discussionmentioning
confidence: 55%
“…Similarly, a 3.7 gene deletion is the most frequently seen mutation in Europe with the allele frequencies of 58.2 % in Holland, 46.94 % in Sicily and 52.41 % in Spain [21]. This is also true for Malaysia (45.9 %), Brazil (10.7 %) and North Thailand (58.3 %) [22]. These results show that -a 3.7 gene deletion is prevalent worldwide including our country and indicate that our results are in agreement with literature.…”
Section: Discussionmentioning
confidence: 94%